Association between chronotype and nonrestorative sleep in a college population. (20th October 2016) - Tutek, Joshua; Emert, Sarah E.; Dautovich, Natalie D.; Lichstein, Kenneth L.
ABSTRACT: Nonrestorative sleep (NRS), characterized by a lack of refreshment upon awakening, has received little attention in the sleep literature even though it can occur and cause impairment apart from other sleep difficulties associated with insomnia. The Restorative Sleep Questionnaire (RSQ) is one of the first validated self-report instruments for investigating NRS severity, presenting new opportunities to explore what factors predict and perhaps contribute to unrefreshing sleep. The present study sought to determine whether inherent circadian preference for morning or evening activity, known as chronotype, predicted restorative sleep in 164 college undergraduates who completed daily RSQs over 2 weeks. The participants who endorsed greater orientation to evening activity on the morningness–eveningness questionnaire reported significantly less average restorative sleep across their full sampling period, and this association was maintained after accounting for demographic factors, number of sleep-relevant psychiatric and medical diagnoses, sleep diary parameters, self-reported status as an insomniac and ratings of sleep quality. When analyses were conducted separately for weekday and weekend RSQ scores, eveningness predicted NRS independently of extraneous variables only during the workweek, not during Saturday and Sunday. These findings have implications for the developing conceptualization of NRS, and continue the work of elucidating the interconnections between common sleep disturbances and the circadian system.